(untitled) (Applied Biological Research, 2017)
The present investigation was carried out to assess genetic variation for some easily observable traits in a set of 64 germplasm lines of Asiatic cotton (Gossypium arboreum L.). The morphological characters included plant body colour, colour of petals and anthers, leaf shape and presence/absence of leaf nectary. Green plant colour, yellow petal and anther colour, digitate leaf shape, and absence of nectary were observed to be predominant morphological characters among the desi cotton lines studied. Of the 64 cotton genotypes evaluated, 56 were observed to have green and eight pigmented plants. Desi cotton genotypes exhibited following petal colours: yellow (38), white (13), variegated (7), cream (4), red (1) and off-white (1). Majority of the genotypes (59) possessed digitate (narrow lobed) leaves. The present study has provided an insight into the genetic variation for some morphological characters in desi cotton genotypes. Though morphological markers have their own limitations, yet these traits being independent of the effects of environment, may be used for the identification of cotton germplasm especially in seed production plots.